2004
DOI: 10.1097/01.aog.0000128049.73556.fb
|View full text |Cite
|
Sign up to set email alerts
|

Late First-Trimester Invasive Prenatal Diagnosis: Results of an International Randomized Trial

Abstract: I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 18 publications
1
44
0
4
Order By: Relevance
“…Early amniocentesis (\ 13 weeks gestation) was associated with an increased risk in talipes equinovarus compared to midgestational amniocentesis or chorionic villus sampling [51]. Increased risk of clubfoot was partially associated with amniotic fluid leakage, suggesting that oligohydramnios occurring at a critical gestational period may be detrimental to foot development [66].…”
Section: Etiologymentioning
confidence: 99%
“…Early amniocentesis (\ 13 weeks gestation) was associated with an increased risk in talipes equinovarus compared to midgestational amniocentesis or chorionic villus sampling [51]. Increased risk of clubfoot was partially associated with amniotic fluid leakage, suggesting that oligohydramnios occurring at a critical gestational period may be detrimental to foot development [66].…”
Section: Etiologymentioning
confidence: 99%
“…On the other hand, portions of two trials had some prospective components (8,22). The report of Silver et al (8) was a secondary analysis of a randomized trial, which was underpowered owing to difficulties in obtaining the necessary sample size (30). In addition, the report of Khalil et al (22) indicated that their trial was part of an ongoing prospective study, but actually the outcomes were acquired retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…14 The achilles tendon may need to be subcutaneously sectioned to facilitate this correction. [15][16] Ponseti developed and refined his method of serial casting in the 1940's, based on the above principles, but kite's method still remained in vogue till a decade back, when the long term results of ponseti were published. In our study before treatment, before the treatment, the mean pirani score for hind foot was 2.39.…”
Section: Discussionmentioning
confidence: 99%